Historiographical Analysis of Social and Educational Support to Children of Vulnerable Groups in the Second Half of the Twentieth Century - Yulia Semenova (Pedagogical Discourse, 2013)
The historiographical analysis of the problem of social and educational support to vulnerable groups of children in Ukraine in the second half of the twentieth century is presented in the article. Historical and pedagogical researches on social and educational support for children of vulnerable groups in the second half of the twentieth century are singled out, which can be classified according to the following thematic directions: research papers regarding forms, methods and organization of social and educational support for children of vulnerable groups in the second half of the twentieth century, achievements of outstanding teachers in the context of the study, research on statistical data concerning the problem of the study.